MODEL PENYELESAIAN PIDANA ADAT MENURUT HUKUM YANG HIDUP DALAM MASYARAKAT DI KOTA BENGKULU - Susi Ramadhani; Asep Suherman; Dwi Putri Lestarika (UNIB Press, 2025)
The promulgation of Law Number 1 of 2023 concerning the national Criminal Code (KUHP), replacing the Dutch Criminal Code, is a fundamental reform of Indonesian criminal law because of the recognition of laws that live in society. The purpose of this study is to find out and describe the position of customary criminal settlement in Indonesian laws and regulations and the process of resolving customary crimes according to the law that lives in the community in Bengkulu City. In Bengkulu City, the customs used are the Lembak custom, the Malay custom, the Serawai custom, and the Rejang custom. The enforcement of Bengkulu City customs was confirmed with the issuance of Regional Regulation Number 29 of 2003 concerning the Enforcement of Bengkulu City Customs. The method used in this study is an empirical legal research method, where data is obtained directly from the community. This research is important because there is no uniformity in the process of resolving customary crimes that occur in Bengkulu City. The contribution given will benefit law enforcement officials in resolving customary crimes in accordance with the laws that live in the community, especially in Bengkulu City as an effort to enforce the law.